Come superare oggi le difficoltà analitiche a cui andarono incontro i chimici dell’Ottocento utilizzando semplici metodi moderni in un laboratorio scolastico - D’Angelo, Giuseppe (Chimica nella Scuola, 2022)
Two simple experiences were carried out in a school laboratory. Even at school it is possible to experimentally determine the percentage composition by mass of an element of a compound and verify the combination ratio between carbon and oxygen in carbon dioxide. This short work describes how it is possible to do today, with simple modern equipment, what the chemists of the nineteenth century achieved by applying the “law of atoms” of the great Italian chemist Stanislao Cannizzaro.